2018
DOI: 10.3390/md16090297
|View full text |Cite
|
Sign up to set email alerts
|

Sesterterpenoid and Steroid Metabolites from a Deep-Water Alaska Sponge Inhibit Wnt/β-Catenin Signaling in Colon Cancer Cells

Abstract: The Wnt/β-catenin signaling pathway is known to play critical roles in a wide range of cellular processes: cell proliferation, differentiation, migration and embryonic development. Importantly, dysregulation of this pathway is tightly associated with pathogenesis in most human cancers. Therefore, the Wnt/β-catenin pathway has emerged as a promising target in anticancer drug screening programs. In the present study, we have isolated three previously unreported metabolites from an undescribed sponge, a species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…17,18 The previous in vitro studies have shown that constituents from CA extract possessed several biological activities, including cytotoxicity. 15 Some of the reported mechanisms possessed by steroids enable them to act as anticancer agents by inhibiting Wnt/ß-catenin signaling in colon cancer, 19 inhibiting PSA expression, and glucose uptake. 20 The proliferation assay data in the present study indicated that CA extract significantly inhibited the proliferation of human lung carcinoma cells A549 after 24 h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The previous in vitro studies have shown that constituents from CA extract possessed several biological activities, including cytotoxicity. 15 Some of the reported mechanisms possessed by steroids enable them to act as anticancer agents by inhibiting Wnt/ß-catenin signaling in colon cancer, 19 inhibiting PSA expression, and glucose uptake. 20 The proliferation assay data in the present study indicated that CA extract significantly inhibited the proliferation of human lung carcinoma cells A549 after 24 h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Two examples of non-latrunculid genera further illustrate the importance of the general taxonomic process: (1) the dereplication of numerous deep-water sponge specimens and the discovery of several new species of Monanchora Carter, 1883 (order Poecilosclerida, family Crambeidae Lévi, 1963) [ 148 ] from the Aleutian Islands, separating these from the northeastern Pacific species, Monanchora pulchra Lambe, 1894 [ 149 ], facilitated the discovery of three metabolites that exhibited potential antiproliferative activity against two CRT-positive colon cancer cell lines [ 150 ]; (2) the elucidation of morphological and colour variation in Acanthostrongylophora ingens Thiele, 1899 [ 151 ] (order Haplosclerida, family Petrosiidae Van Soest, 1980) [ 152 ] and revision of the classification of the numerous specimens that have yielded manzamines and related compounds in the literature, over many years [ 152 ] facilitated the discovery of a sponge-associated bacterium that produces the manzamine class of antimalarials in A. ingens Thiele, 1899 [ 152 ].…”
Section: The Significance Of Pyrroloiminoquinone-type Alkaloids Inmentioning
confidence: 99%
“…Both acted by promoting proteasomal degradation of β-catenin (induced by Wnt3a or a GSK3β inhibitor) and both affected expression of a series of Wnt target genes. More sponge metabolites of the sesterpenoid and steroid nature showed Wnt-inhibiting activities in luciferase assays [206]; sponge-derived quinones decreased β-catenin levels in HEK293 cells [207], identifying marine sponges as an interesting new source of potential Wnt inhibitors. TOPFlash-based high throughput screening of Pacific invertebrate extracts identified Wnt-inhibiting activities from holothurians Peniagone sp.…”
Section: Wnt Inhibitors From Natural Sourcesmentioning
confidence: 99%
“…Aeroplysinin-1 (brominated tyrosine) Promotes the proteasomal degradation of intracellular β-catenin - [205] Sesterterpenoid and Steroid Metabolites [206] Quinones - [207] Extract - [96] Holothuria…”
Section: Inotodiol (Lanostane Triterpenoid)mentioning
confidence: 99%